2019
DOI: 10.3390/cancers11020208
|View full text |Cite
|
Sign up to set email alerts
|

ORAI1 and ORAI3 in Breast Cancer Molecular Subtypes and the Identification of ORAI3 as a Hypoxia Sensitive Gene and a Regulator of Hypoxia Responses

Abstract: The remodeling of specific calcium-permeable ion channels is a feature of some breast cancer subtypes. ORAI1 is a protein that forms a calcium-permeable ion channel responsible for store-operated calcium entry (SOCE) in a variety of cell types. ORAI3, a related isoform, is not a regulator of SOCE in most cell types. However, ORAI3 does control SOCE in many estrogen receptor-positive breast cancer cell lines, where it also controls proliferation. ORAI1 is a well-characterized regulator of the proliferation and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
51
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(54 citation statements)
references
References 66 publications
3
51
0
Order By: Relevance
“…The disruption of SOCE has various pathophysiological implications such as muscle, immune, and neurodegenerative disorders as well as cancer [ 12 , 13 , 14 , 15 , 16 ]. Breast cancer metastasis has been linked to STIM1/Orai1-mediated Ca 2+ influx [ 17 ] and several studies also highlighted the upregulation of STIM1 and Orai1 in basal breast cancers [ 18 , 19 ]. Our understanding on the remodeling of SOCE in breast cancer cells has increased over the years and has recently been reviewed [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…The disruption of SOCE has various pathophysiological implications such as muscle, immune, and neurodegenerative disorders as well as cancer [ 12 , 13 , 14 , 15 , 16 ]. Breast cancer metastasis has been linked to STIM1/Orai1-mediated Ca 2+ influx [ 17 ] and several studies also highlighted the upregulation of STIM1 and Orai1 in basal breast cancers [ 18 , 19 ]. Our understanding on the remodeling of SOCE in breast cancer cells has increased over the years and has recently been reviewed [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, this type of cancer is resistant to hormonal therapies and chemicals that target the HER2 receptor [1]. Studies in TNBC cells revealed that Ca 2+ signaling is remodeled and plays a key functional role [2][3][4][5]. TNBC cells overexpress Orai1, which is responsible for the activation of store-operated Ca 2+ entry (SOCE) [6].…”
Section: Introductionmentioning
confidence: 99%
“…In estrogen receptor-positive breast cancer cells, but not in estrogen receptor-negative breast cancer cells; however, ORAI3 expression levels are increased (Motiani et al 2010). Assessment of clinical samples shows higher levels of ORAI3 in luminal breast cancer subtypes compared with the basal molecular subtype, which overlap with estrogen receptor-positive and estrogen receptor-negative breast cancer subtypes, respectively (Azimi et al 2019). Unlike in most other cell types, and in contrast to the estrogen receptor-negative breast cancer cell lines tested, the overexpression of ORAI3 in estrogen receptorpositive breast cancer cells is associated with ORAI3 also contributing along with ORAI1 to SOCE (Motiani et al 2010).…”
Section: Remodeling Of the Calcium-signaling Toolkit In Cancer Cellsmentioning
confidence: 99%